Abnormal glucose tolerance is associated with preterm labor and increased neonatal complications in Taiwanese women - Panchalli Wang; Mei-Chun Lu; Yuan-Horng Yan (Elsevier, 2013)
Objective: To investigate the relationship between abnormal degrees of oral glucose tolerance test (OGTT) results and pregnancy outcomes. Materials and methods: A total of 7513 singleton pregnancies screened for gestational diabetes mellitus were enrolled in this retrospective observational study. The pregnancy outcomes of six different groups with different degrees of glucose intolerance using the OGTT were compared [both the National Diabetes Data Group (NDDG) and Carpenter and Coustan (C&C) criteria were used]. The pregnancies were classified into the following groups: the normal group, consisting of pregnancies with a negative 50-g glucose challenge test (GCT), and Grade 0, 1, 2, 3 and 4 groups, consisting of pregnancies with positive 50-g GCT, and abnormal values of 0, 1, 2, 3 and 4 from the 100-g OGTT, respectively. Results: The adjusted odds ratios (95% confidence interval) for preterm labor and admission to the neonatal intensive care unit (NICU) were shown to be increased in the Grade 4 groups [3.31 (1.47-7.43) and 6.31 (3.14-12.70) by the NDDG criteria; 4.13 (2.30-7.43) and 5.25 (3.00-9.19) by the C&C criteria] compared with the normal group. Conclusion: The results indicated an increased risk for preterm labor and admission to the NICU as the abnormal value of the OGTT increased.